2020
DOI: 10.1101/2020.08.29.20184093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the Risk of Indoor Drainage System in Multi-unit Apartment Building as a Transmission Route of SARS-CoV-2

Abstract: The COVID-19 pandemic has had a profound impact on human society. The isolation of SARS-CoV-2 from patients feces on human cell line raised concerns of possible transmission through human feces including exposure to aerosols generated by toilet flushing and through the indoor drainage system. Currently, routes of transmission, other than the close contact droplet transmission, are still not well understood. A quantitative microbial risk assessment was conducted to estimate the health risks associated with two … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…Prior studies have demonstrated the paths of vertical transmission between vertically aligned flats, and the transmission could be related to the stack effect. For COVID-19 clusters involving vertical transmission in buildings, virusladen aerosols are primarily transmitted via wastewater plumbing systems (Shi et al 2021;Wang et al 2022a). Drainpipes are not sealed as tightly as pipes for pressurised water supplies, which can lead to long-term and occasional leakages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated the paths of vertical transmission between vertically aligned flats, and the transmission could be related to the stack effect. For COVID-19 clusters involving vertical transmission in buildings, virusladen aerosols are primarily transmitted via wastewater plumbing systems (Shi et al 2021;Wang et al 2022a). Drainpipes are not sealed as tightly as pipes for pressurised water supplies, which can lead to long-term and occasional leakages.…”
Section: Introductionmentioning
confidence: 99%
“…Drainpipes are not sealed as tightly as pipes for pressurised water supplies, which can lead to long-term and occasional leakages. Flushing a toilet can temporarily alter the pressure inside drainpipes, leading to the infiltration of virus-laden aerosols into or out of the drainpipes if pipe leakage occurs (Shi et al 2021;Wang et al 2022a). In addition, differences in temperature or humidity between the inner and outer environments of a leaky drainage stack can produce the typical or reverse stack effect, which produces vertical airflow in the drainage stack and promotes air exchange between flats sharing the same drainage stack (Mijorski and Cammelli 2016;Magyar 2022).…”
Section: Introductionmentioning
confidence: 99%